PRESENT STATE OF OCEAN OBSERVATIONS AND SERVICE IN VIETNAM - Mau, Le Dinh; Lam, Tran Hong; Cuong, Nguyen Manh (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents the basic information on the present status of ocean observation and service in Vietnam with focus on the physical oceanography area. Study results show that in recent years, ocean observations of Vietnam have been equipped with a series of modern measured and analyzed instruments, especially at related offices of the Vietnam Academy of Science and Technology (VAST) and Ministry of Natural Resources and Environment (MONRE). The remarkable progress was to carry out the UAV (Unmanned Aerial Vehicle) program to observe oceanographic conditions in nearshore region by VAST from 2013. Earlier, from 2009 the MONRE carried out the program to establish a network of stations to observe waves and current characteristics in nearshore region by high frequency radar technology. However, the current status of ocean observations and services in Vietnam still has shortcomings in both manpower and equipment and the observations are mostly focused in the nearshore region. Services on oceanographic data are still less professional and public. For sustainable development of ocean observations and service, it is necessary to promote international cooperation projects on oceanography especially in the frame-work of IOC/WESTPAC cooperation.